Chlamydia trachomatis infection in dizygotic twins delivered by caesarean section. Issue 5 (October 1988) - Bell, T A
Abstract : Chlamydia trachomatis was isolated from the conjunctiva, pharynx, and rectum of one 10 day old twin delivered by caesarean section without prior rupture of the chorioamnion and from the pharynx of her brother. The means by which C trachomatis causes such infection is not known.